Competitive Advantage Development Model with Logistics Competence - Sodikin, Mohamad; Susilowati, Susilowati (Journal of Digital Marketing and Halal Industry, 2024)
Uniqueness in the field of logistics was chosen as the basis for excellence in higher education at Institute of Economics Science Cendekia Karya Utama in Indonesia, because it is considered that logistics capabilities are the basis for building competitive advantages for its alumni. However, this program has never been studied for the effectiveness of its implementation and also for its follow-up development model. Based on the Resource Based View theory, this research aims to determine the effectiveness of the logistics competency program and build a competitive development model at Institute Economic Science Cendekia Karya Utama Semarang. Through qualitative methods involving informants from the Indonesian Logistics Training Institute, lecturers, logistics practitioners and graduate who work in logistics companies, it was found that to increase broader competitive advantage there needs to be strengthening in several aspects, namely the need to add digital logistics curriculum content (ex: warehouse management system, transportation management system and strengthening foreign languages (English, Mandarin). A logistics-based competitive advantage development model can be developed by synergizing and collaborating between universities and alumni, the business and industrial logistics, practitioners and training institutions according to their respective roles -each of which is discussed in this study. This study contributes to the expansion of the resource based view theory and the development of graduate quality and unique logistics competencies as a basis for building excellence from Institute Economic Science Cendekia Karya Utama Semarang, Indonesia